Sportspecific performance diagnosis in ski mountaineering - comparison of a sportspecific cardiopulmonary exercise test on a treadmill versus outdoors and at altitude, a pilot study - Isabelle Schöffl; Bernhard Bliemsrieder; Thomas Küpper; Volker Schöffl (University of Applied Sciences in Tarnow, Poland, 2021)
Background: Ski mountaineering is a competitive sport that has gained popularity during the last years. As most competitions are held in altitudes between 1500 m and 3500 m, a considerable amount of training occurs at various hypobaric hypoxia degrees. It was establishing a sport-specific cardiopulmonary exercise protocol using standard ski mountaineering equipment on a treadmill. This study investigated altitude's effects on a self-regulated incremental exercise field test at 3100 m with this protocol. Methods: Six athletes were tested (24.2 ± 4.2 years) from the German Ski Mountaineering National Team with a portable telemetric cardiopulmonary exercise test equipment. First, an incremental indoor step test with skis on a treadmill (altitude 310 m) and four days later outdoor on glacier snow (3085 m) after three days of acclimatization. All athletes were exposed to repetitive intermittent hypoxia during the weeks before the test. Standard cardiopulmonary exercise parameters were recorded while individual training zones were defined according to ventilatory thresholds. Results: In highly trained athletes, mean V̇O2peak (72/ml kg KG/min) was reduced by 25% or 9% per 1000 m altitude gain and by 18% and 23% at the first and second ventilatory thresholds, respectively. Mean maximum heart rate and the heart rate at the ventilatory thresholds were reduced at altitude compared to sea-level, as was the O2pulse. Conclusion: Due to distinctive individual reactions to hypoxia, cold, etc., an individual and sport-specific field performance analysis, representing the daily training environment, is highly useful in world-class athletes for precise training control. Our self-regulated cardiopulmonary field protocol could well prove to serve in such a way.